Red vs. White Edible Bird’s Nests: Oxidative Processing Drives Nitrite Disparity and Food Safety Risks - Febriansyah, Muhammad Irfan; Ramadina, Shifa Aulia (Journal of Nutrition Science, 2024)
This study investigates nitrite concentration disparities between red and white edible bird’s nests (EBNs), driven by oxidative processes linked to post-harvest washing protocols. Utilizing a randomized block design, ten EBN samples (five red, five white) were collected from a processing facility in Sidoarjo, Indonesia. Red EBNs were sourced from discontinued stock, while white EBNs were obtained from current production batches. Nitrite levels were quantified using UV-Vis spectrophotometry (541 nm), with statistical analysis performed through two-way ANOVA (α = 0.05) and effect size calculations (Cohen’s *d*). Results revealed a 5.7-fold higher nitrite concentration in red EBNs (88.87 ± 12.42 ppm) compared to white EBNs (15.48 ± 4.44 ppm; *p* < 0.05), with a very large effect size (Cohen’s *d* = 6.24) and 93% variance explained by nest type (η² = 0.93). The oxidative degradation of tyrosine residues during intensive washing, coupled with iron-mediated catalysis and environmental factors, was identified as the primary driver of nitrite accumulation in red nests. Despite compliance with Indonesia’s safety threshold (200 ppm), the elevated nitrite levels raise concerns about nitrosamine formation in acidic gastric environments, necessitating mitigation strategies such as polyphenol integration and optimized drying protocols. This study highlights the critical influence of processing practices on nitrite dynamics and underscores the need for standardized protocols to align with stringent international standards. Future research should address endogenous nitrite sources, microbial contributions, and environmental parameter impacts to enhance food safety and industry sustainability.